The Use of Headspace Solid-Phase Microextraction (HS-SPME) to Assess the Quality and Stability of Fruit Products: An Example Using Red Mombin Pulp (Spondias purpurea L.) - Todisco, Katieli Martins [UNESP]; Castro-Alves, Victor Costa; Garruti, Deborah dos Santos; Correia da Costa, Jose Maria; Clemente, Edmar (Mdpi Ag, 2014)
The present study aimed to evaluate the volatiles profile of red mombin (Spondias purpurea) pulp and its powder produced by spray-drying (SD) as an example to show utility of headspace solid-phase microextraction (HS-SPME) in the analysis of parameters such as the quality and stability of fruit products. Volatiles profiles of the pulp were identified by gas chromatography-mass spectrometry (GC-MS), quantified by gas chromatography-flame ionization detector (GC-FID) and compared to the profile of the powder stored at 0, 60 and 120 days in plastic (PP) or laminated packages (LP). The results showed that the technique was able to identify 36 compounds in the red mombin pulp, 17 out of which have been described for the first time in this fruit, showing that red mombin fresh pulp appears to be unique in terms of volatiles composition. However, only 24 compounds were detected in the powder. This decrease is highly correlated (r(2) = 0.99), at least for the majority of compounds, to the degree of volatility of compounds. Furthermore, the powder stored in PP or LP showed no statistical differences in the amounts of its components for a period of 120 days of storage. Finally, this work shows how HS-SPME analysis can be a valuable tool to assess the quality and stability of fruit products.
Keywords: volatiles profile; headspace solid-phase microextraction; spray-drier; gas chromatography; fruit powder